The effects of different warm-up loads [routines] at equal total workload for high intensity exercise performance - Takizawa, K.; Ishii, K. (International Journal of Sport & Health Science, 2006)
It is well known that warm-up (W-up) routines improve exercise performance and that the duration and intensity of W-up affects high intensity aerobic exercise performance. Previous studies have suggested that intensity and/or duration of W-up affect high intensity aerobic exercise performance, but the total workloads used in those studies were different. In this study, the effects of W-ups of different intensities upon the equal total workloads of high intensity aerobic exercise performance were investigated. Subjects performed three exercise tests under differing W-up conditions. These conditions were firstly W-up at lactate threshold (LT), secondly at 50%LT and thirdly, at the onset of blood lactate accumulation (OBLA). The total workload of each W-up was the equal as 15 minutes at LT. Following a 5-min rest period after completion of W-up, each subject performed a cycling exercise test at 100% V02peak until experiencing exhaustion. The duration of the exercise test was used as an index of exercise performance. Vastus lateralis and rectal temperatures of each subject were measured. No significant differences were observed at vastus lateralis (50%LT; 36.8+/-0.4 °C, LT; 37.2+/-0.5 °C, OBLA; 37.4+/-0.3 °C, p>0.05) or rectal (50%LT; 37.0+/-0.3 °C, LT; 37.2+/-0.4 °C, OBLA; 37.4+/-0.4 °C, p>0.05) temperatures after performing W-up at any of the three different intensities. Similarly, significant differences were observed at exercise test duration between W-up conditions (50%LT; 214.1+/-84.4 sec, LT; 306.7+/-125.5 sec, OBLA; 274.4+/-118.0 sec, p>0.05). These results suggest that if total workloads are the equal and rises in body temperature are similar, W-ups of different intensities have the same effect on high intensity aerobic exercise performance.